Breaking boundaries in biodegradable packaging: a comprehensive review on magnetic alignment of iron-cellulose in PLA - Siti Hajar, Omar; Mohd Aizudin, Abd Aziz; Saiful Azhar, Saad; Khairuddin, Md Isa; Nur Amira Fatihah, Bashari; Muhammad Auni, Hairunnaja (Penerbit UNIMAP, 2025)
This review paper explores the transformative potential of incorporating iron-coated cellulose into polylactic acid (PLA) composite films, presenting a comprehensive analysis of the advancements, implications, and challenges associated with this innovative approach. The introduction establishes the context, emphasizing the growing significance of sustainable packaging and the unique properties offered by biopolymers. The subsequent sections delve into the synthesis and fabrication methods, emphasizing the pivotal role of iron-coated cellulose in enhancing the mechanical, magnetic, and barrier properties of PLA nanocomposites. The review discusses in detail the magnetic alignment techniques employed, elucidating their impact on particle distribution and alignment within the PLA matrix. The exploration of magnetic field application reveals intricate relationships with curing times, emphasizing the dynamic interplay between magnetic alignment, curing processes, and particle distribution. The mechanical properties section further underscores the positive influence of magnetic alignment on tensile strength, stiffness, and dimensional stability, offering promising avenues for oriented structures in structural and functional materials. Expanding the scope to water barrier properties, the review investigates the effects of iron-coated cellulose on moisture absorption, revealing nuanced interactions that enhance the water barrier characteristics of the nanocomposites. Contact angle measurements provide insights into the surface properties, with the study uncovering how magnetic alignment contributes to improved hydrophobicity, thereby resisting water absorption and enhancing the effectiveness of these materials in packaging applications. The implications for sustainable packaging constitute a critical aspect of the review, shedding light on the environmental benefits and challenges associated with implementing magnetic alignment on a larger scale. The optimized material usage, renewable nature of iron-coated cellulose, and potential reduction in waste align with sustainability goals. However, challenges such as specialized equipment requirements and disposal considerations are also discussed, providing a balanced perspective. The paper concludes by summarizing the key advancements achieved through the incorporation of iron-coated cellulose into PLA composite films. It highlights the potential of these nanocomposites for future sustainable packaging, emphasizing their robust mechanical properties, magnetic functionalities, and enhanced water barrier characteristics. The conclusions underscore the collaborative effects of cellulose and iron coating, envisioning a future where sustainable packaging not only meets but surpasses industry standards. In essence, this review paper serves as a comprehensive guide, consolidating knowledge and insights to pave the way for future research and industry practices in the realm of sustainable and enhanced biopolymer packaging.